National Surgical, Obstetric, and Anesthesia Plans: Bridging the Cardiac Surgery Gap - Vervoort, Dominique (The Thoracic and Cardiovascular Surgeon, 2020)
Six billion people worldwide lack access to safe, timely, and affordable cardiac surgical care when needed, despite cardiovascular diseases remaining the world's leading cause of mortality. The large surgical backlog of rheumatic heart disease, stable and high incidence of congenital heart disease, and growing burden of ischemic heart disease around the world calls for urgent scaling of cardiovascular services beyond mere prevention. National Surgical, Obstetric, and Anesthesia Plans are being developed by countries as holistic health systems interventions to increase access to surgical care, but to date, limited to no attention has been given to the inclusion of cardiovascular care.
Keywords: global health; global surgery; governance